2006
DOI: 10.1021/ja058420h
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Frequency High-Field EPR Study of Iron Centers in Malarial Pigments

Abstract: The multi-frequency high-field electron paramagnetic resonance (HFEPR) was used to study the magnetic properties of malarial pigment hemozoin and its synthetic analogue, β-hematin. (FeIII−protoporphyrin−IX)2 dimers containing five-coordinate high-spin FeIII, S = 5/2, are the building blocks of these pigments. The fit of EPR spectra that were acquired in an unprecedented wide range of microwave frequencies of 34 and 94 GHz for hemozoin and 27−500 GHz for β-hematin yielded a complete set of intrinsic spin Hamilt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 21 publications
3
40
0
Order By: Relevance
“…The final system to be mentioned briefly is HS d 5 92 Ligand-field analyses were not performed in these studies, which focused on the detailed EPR experiments. Fe III is of the greatest interest, but in porphyrinic complexes often exhibits large ZFS, due to the highly tetragonally distorted geometry.…”
Section: -83mentioning
confidence: 99%
See 3 more Smart Citations
“…The final system to be mentioned briefly is HS d 5 92 Ligand-field analyses were not performed in these studies, which focused on the detailed EPR experiments. Fe III is of the greatest interest, but in porphyrinic complexes often exhibits large ZFS, due to the highly tetragonally distorted geometry.…”
Section: -83mentioning
confidence: 99%
“…An EPR transition near zero-field directly yielded 2|D| = 11.7 cm -1 . 92 Note also the use of ENDOR spectroscopy to determine ZFS in HS Fe III heme proteins, 75 as mentioned above.…”
Section: -83mentioning
confidence: 99%
See 2 more Smart Citations
“…The determination of the relationship between the external macroscopic morphology of the crystal (crystal habit) and the unit cell structure by Buller et al (2002) (Figure 3) has been important in later work that has attempted to understand the molecular mechanism of haemozoin formation. Magnetic properties have been investigated using X-band electron paramagnetic resonance (EPR) spectroscopy and magnetic Mössbauer spectroscopy and have unequivocally demonstrated that the Fe(III) centre exists in a high spin S = 5 / 2 state (Bohle et al 1998) with very weak to negligible magnetic exchange between Fe(III) centres later confirmed by multifrequency high field EPR (Sienkiewicz et al 2006). The uv-visible spectrum of -haematin has also been determined and its luminescence properties investigated (Bellemare et al, 2009).…”
Section: Physical Properties and Spectroscopymentioning
confidence: 99%